NYAI EVA: AGEN KESETARAAN GENDER DAN PEMBERDAYAAN PEREMPUAN DI KABUPATEN SUMENEP - Ahmadi, Ahmadi (Kafa`ah: Journal of Gender Studies, 2023)
As adherents of a patriarchal culture, Madurese society places women as part of the family who must be protected, cared for and fought for by men. Madurese women are in a different space from men. Since the presence of Dewi Khalifah (Nyai Eva) in political contestation, it has become a phenomenon in itself as the first woman to occupy the highest public office in a district in Madura. The main problem of this article is related to Nyai Eva's role as an agent of gender equality and women's empowerment in Sumenep Regency. This phenomenon is dissected using qualitative methods with a series of scientific work processes which include observation, interviews and documentation. The role theory proposed by Kozier Barbara is used as an analytical tool. The findings of this research show that Nyai Eva plays a role in building gender equality and women's empowerment in the fields of education and economics in Sumenep Regency. Nyai Eva's success was supported by her social status as a respected woman in Madurese society.